Diagnostic and Prognostic Research - Collins, Gary; Cooks, Nancy; Moons, Karel
Diagnostic and Prognostic Research encompasses diagnostic and prognostic research addressing studies on the evaluation of medical tests, markers, prediction models, decision tools and apps. Diagnostic and Prognostic Research provides a platform for disseminating empirical primary studies, systematic reviews (including meta-analyses) as well as articles on methodology, protocols and commentaries addressing diagnostic and prognostic studies. The journal ensures that the results of all well-conducted diagnostic and prognostic research are published, regardless of their outcome.